Peran Media Pembelajaran dalam Komunikasi Instruksional Sekolah Vokasi Pariwisata di Jawa Barat - Diana Simanjuntak; Darmawan Sunarya (STIEPAR YAPARI Bandung, 2022)
Learning media as a tool to convey messages or information in the instructional communication process should be able to stimulate attention, interest and improve student memory. For this reason, designing and using learning media is important so that the delivery of learning messages can be achieved effectively. This study aims to find out the importance of the role of learning media in the instructional communication process in the field of tourism expertise in several vocational schools, vocational schools and universities in West Java. The research was conducted qualitatively with the aim of obtaining open and detailed data from informants who expressed their opinions about the learning media used by their teachers/lecturers. The key informants consisted of 24 students from six vocational schools and four universities in West Java, while data triangulation was carried out to 10 lecturers/teachers. The results of the analysis of the four aspects studied show: a. Students really feel the benefits and functions of learning media. b. The availability of learning media in three schools is complete and institutionalized, but in the other seven schools it still depends on the initiative of each teacher. c. Student/student responses to learning media greatly encourage the spirit of learning, it is easier to understand and remember learning materials. d. Barriers to the provision of learning media: limited educational background and experience of teachers/lecturers in the field of pedagogy, limited initiative and creativity of certain teachers/lecturers, not yet requiring teachers to provide media in every lesson, limited school facilities, such as internet networks and LCD projectors. This condition illustrates that this tourism vocational school has not fully designed its learning media properly, because there are differences in the availability of learning media between schools and between teachers, including differences in the level of attractiveness, diversity, suitability and creativity of lecturers/teachers in providing and using them. As a tourism vocational school whose graduates must be ready to work with work competencies that include knowledge, skills and professional work attitudes with a hospitality spirit formed in schools through the learning process. There are three schools that have achieved this well, while the other seven schools still need to improve the quality of learning. through appropriate learning media and based on the competencies and needs of the world of work. The results of this study are expected to be an important input for the implementation of West Java tourism vocational schools.